The National Niemann-Pick Type C1 Disease Database: correlation of lipid profiles, mutations, and biochemical phenotypes - Garver, William S. (The American Society for Biochemistry and Molecular Biology, 2010)
Niemann-Pick type C1 disease (NPC1) is an autosomal recessive lysosomal storage disorder characterized by neonatal jaundice, hepatosplenomegaly, and progressive neurodegeneration. The present study provides the lipid profiles, mutations, and corresponding associations with the biochemical phenotype obtained from NPC1 patients who participated in the National NPC1 Disease Database. Lipid profiles were obtained from 34 patients (39%) in the survey and demonstrated significantly reduced plasma LDL cholesterol (LDL-C) and increased plasma triglycerides in the majority of patients. Reduced plasma HDL cholesterol (HDL-C) was the most consistent lipoprotein abnormality found in male and female NPC1 patients across age groups and occurred independent of changes in plasma triglycerides. A subset of 19 patients for whom the biochemical severity of known NPC1 mutations could be correlated with their lipid profile showed a strong inverse correlation between plasma HDL-C and severity of the biochemical phenotype. Gene mutations were available for 52 patients (59%) in the survey, including 52 different mutations and five novel mutations (Y628C, P887L, I923V, A1151T, and 3741_3744delACTC). Together, these findings provide novel information regarding the plasma lipoprotein changes and mutations in NPC1 disease, and suggest plasma HDL-C represents a potential biomarker of NPC1 disease severity.